1983
DOI: 10.1128/jb.156.3.1135-1143.1983
|View full text |Cite
|
Sign up to set email alerts
|

Action of CAP on the malT promoter in vitro

Abstract: DNase I footprinting experiments demonstrated that CAP, the cyclic AMP receptor protein of Escherichia coli, binds around position -70 at the promoter of malT, the positive regulator gene of the maltose regulon. The binding of CAP in the presence of cyclic AMP favored the subsequent specific binding of RNA polymerase. Initiation of malT transcription in vitro displayed an absolute requirement for CAP at all tested RNA polymerase concentrations. However this was not the case with a mutant promoter (malTpl), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Run-off assays The assays reported above indicated that similar amounts of competent complex were formed at malT in the absence and presence of CRP. These results, obtained by monitoring the formation of a trinucleotide, were at striking variance with the single-round transcription experiments reported by Chapon and Kolb (1983), who found a significant increase in the amount of full-length transcripts synthesized when CRP was added. Run-off experiments were therefore performed under conditions analogous to the abortive initiation assays.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Run-off assays The assays reported above indicated that similar amounts of competent complex were formed at malT in the absence and presence of CRP. These results, obtained by monitoring the formation of a trinucleotide, were at striking variance with the single-round transcription experiments reported by Chapon and Kolb (1983), who found a significant increase in the amount of full-length transcripts synthesized when CRP was added. Run-off experiments were therefore performed under conditions analogous to the abortive initiation assays.…”
Section: Resultssupporting
confidence: 61%
“…Organization of the DNA region upstream the RNA start at malT As already shown in Chapon and Kolb (1983), the malT promoter is extremely weak in the absence of added CRP -cAMP complex. Run-off transcription assays, performed under their conditions on the 190-bp Sall -Hinfl fragment depicted in Figure 1, yielded several faint sets of long transcripts (n > 10) ( Figure 6).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Figure 2A and B shows the footprinting patterns of the coding and template strands, respectively. CRP binds to a region between -60 and -80 in the presence of cAMP as reported by Chapon and Kolb (1983). When RNAP alone was incubated with the malT DNA, a region between ϩ20 and -60 was protected against DNase I digestion.…”
Section: Protein-dna Interaction In the Complexes At The Malt Promotermentioning
confidence: 60%